AMBIVALENSI PENGATURAN PEMILIHAN UMUM DI INDONESIA - Yusdar Yusdar (Al-Adalah: Jurnal Hukum dan Politik Islam, 2019)
This study aims to understand the ambivalence of organizing elections in Indonesia so that they can conceptualize the ideal setting for conducting general elections with integrity. This research is normative legal research (normative legal research). This research was conducted by examining primary legal material and secondary legal material.The results of the study indicate that the regulation of elections used in the administration of elections in Indonesia only emphasizes the regulation of procedural aspects. Whereas the indicators of the success of the election if the election organizers, election participants and the public as voters carry out the stages of the election in accordance with the rules of the election stage even though they set aside substantial aspects. Therefore, arrangements are needed in the administration of elections that emphasize substantial aspects, so that elections with integrity can be realized.